How to Grow and Survive without Zinc Oxide in Pig Production? A Comparative Study with STODI (Global Journal of Medical Research, 2022)
During weaning piglets are exposed to a range of stressors all of which cause gastrointestinal and immune system issues Post-Weaning Diarrhoea PWD is a multifactorial illness characterized by the frequent secretion of watery faeces which can cause stunt growth morbidity and even death STODI is the most incredible option for ZnO to reduce PWD and increase pig growth performance in the first few weeks after weaning STODI is a polyherbal combination including Acacia nilotica Andrographis paniculata Holarrhena antidysenterica Punica granatum and Terminalia bellirica This can lower the incidence of diarrhoea and promote the growth of the piglet
Keywords: piglet; post-weaning diarrhoea; STODI® and ZnO